Adaptação transcultural do ghent developmental balance test, confiabilidade e validade concorrente de sua versão em língua portuguesa para crianças pré-escolares - Bizinotto, Thailyne (2015)
One of the importante skills of children in school age is the balance, important for maintaining bipedal posture as opposed to the constant action of gravity. The objectives of this study were to cross-cultural adapt, verify the reliability and concorrent validity the Development Test Balance Ghent (TDEG) for children between 22 months and 6 years. This study evaluated 47 children between 22 months and 6 years old of both sexes in Goiânia. The instruments used were: Ghent Developmental Balance Test (GDBT); Gross Motor Function Classification System (GMFCS); Sitting-Rising Test (TSL); Denver II Developmental Screening Test; Pediatric Balance Scale (EEP). To check the inter-observers reliability, the assessment of children was videotaped and passed to four (4) observers. To check the intra-observer reliability, a new evalluation through the videos was performed six (6) months after the first score. In order to determine the intra-rater reliability, a second evaluation of the child was performed up to 30 days after the first evaluation. After the translation into Portuguese some terms were discussed and consensus was carried out, some of which related to the content and semantics were changed to become the test more understandable and appropriate. The results of intra-rater reliability analysis of the TDEG total score was excellent, provided ICC = 0.94 . The inter-observers reliability of the TDEG total score of and TSL can be considered excellent withICC = 0.98 and 0.85, respectively. The inter-observers agreement of the EEP total score was considered moderate, with ICC = 0.56. By correlating TDEG with the EEP considering the entire sample, it was found an r = 0.70 (p <0.001), indicating a strong and significant correlation between these instruments. Analysing the second instrument used for validation, a moderate correlation with r = 0.42 and significant (p = 0.005) between TDEG and TSL was found when considering the entire sample. From these results we conclude that the TDEG has concurrent validity and is reliable for use in the age group which it proposes to assess, especially in the total score. Furthermore, the TDEG is a good tool for scientific research and ambulatory care about balance disorders of children under five years old.